2021
DOI: 10.1016/j.jbc.2021.100650
|View full text |Cite
|
Sign up to set email alerts
|

Interferon regulatory factor 8 regulates expression of acid ceramidase and infection susceptibility in cystic fibrosis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Previous studies demonstrated that low levels of sphingosine are sufficient to treat or prevent pulmonary infections, at least in mice, in particular mice with cystic fibrosis [ 15 , 17 , 39 ]. Cystic fibrosis mice exhibit a constitutive decrease of sphingosine in bronchial epithelial cells, which is caused by an IRF-8-regulated down-regulation of acid ceramidase expression in Cftr-deficient bronchial epithelial cells [ 40 ]. The lack of sphingosine resulted in increased infection susceptibility of CF-mice, which was corrected by inhalation of sphingosine [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that low levels of sphingosine are sufficient to treat or prevent pulmonary infections, at least in mice, in particular mice with cystic fibrosis [ 15 , 17 , 39 ]. Cystic fibrosis mice exhibit a constitutive decrease of sphingosine in bronchial epithelial cells, which is caused by an IRF-8-regulated down-regulation of acid ceramidase expression in Cftr-deficient bronchial epithelial cells [ 40 ]. The lack of sphingosine resulted in increased infection susceptibility of CF-mice, which was corrected by inhalation of sphingosine [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cystic fibrosis mice exhibit a constitutive decrease of sphingosine in bronchial epithelial cells, which is caused by an IRF-8-regulated down-regulation of acid ceramidase expression in Cftr-deficient bronchial epithelial cells [ 40 ]. The lack of sphingosine resulted in increased infection susceptibility of CF-mice, which was corrected by inhalation of sphingosine [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…NTRK3 [81], MMP9 [82], IGF2 [83], SOCS3 [84], IGFBP2 [85], SLC1A3 [86], NOS1AP [87], HP (haptoglobin) [88], TLR5 [89], ARG1 [90], NRG1 [91], RGS5 [92], LCN2 [93], TSPO (translocator protein) [94], PLAU (plasminogen activator, urokinase) [95], MME (membrane metalloendopeptidase) [96], BST1 [97], NR6A1 [98], TLR4 [99], NRN1 [100], ABCA13 [101], CTSD (cathepsin D) [102], NCAM1 [103], SIGMAR1 [104], CNR2 [105], CCR4 [106], ABCB1 [107], TIMELESS (timeless circadian regulator) [108], IRF8 [109], TXNIP (thioredoxin interacting protein) [110], SUV39H1 [111], CRY1 [112], CRY2 [113], PDCD4 [114] and MGAT5 [115] played an important role in depression and anxiety. Accumulating evidence has demonstrated that MMP9 [116], S100A12 [117], HP (haptoglobin) [118], TLR5 [119], NRG1 [120], PLAU (plasminogen activator, urokinase) [121], SLC11A1 [122], AQP9 [123], CHIT1 [124], TLR4 [125], SLC26A8 [126], CTSD (cathepsin D) [127], SERPINB1 [128], FASLG (Fas ligand) [129], SLC4A4 [130], AQP3 [131] and IRF8 [132] appears to be constitutively associated with CF . MMP9 [133], S100A12 [134], SOCS3 [135], MMP8 [136], CRISP3 [137], S100A9 [138], RETN (resistin) [139], IL1RN [140], TLR4 [141], GGT1 [142], CTSD (cathepsin D) [143], FASLG (Fas ligand) [144], CCR4 [145], FCRL3 [146] and ABCF1 [147] were revealed and regarded as diagnostic biomarker in pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…CHGA (chromogranin A) [48] and IL23R [49] [99], NRN1 [100], ABCA13 [101], CTSD (cathepsin D) [102], NCAM1 [103], SIGMAR1 [104], CNR2 [105], CCR4 [106], ABCB1 [107], TIMELESS (timeless circadian regulator) [108], IRF8 [109], TXNIP (thioredoxin interacting protein) [110], SUV39H1 [111], CRY1 [112], CRY2 [113], PDCD4 [114] and MGAT5 [115] played an important role in depression and anxiety. Accumulating evidence has demonstrated that MMP9 [116], S100A12 [117], HP (haptoglobin) [118], TLR5 [119], NRG1 [120], PLAU (plasminogen activator, urokinase) [121], SLC11A1 [122], AQP9 [123], CHIT1 [124], TLR4 [125], SLC26A8 [126], CTSD (cathepsin D) [127], SERPINB1 [128], FASLG (Fas ligand) [129], SLC4A4 [130], AQP3 [131] and IRF8 [132] appears to be constitutively associated with CF. MMP9 [133], S100A12 [134], SOCS3 [135], MMP8 [136], CRISP3 [137], S100A9 [138], RETN (resistin) [139], IL1RN [140], TLR4 [141], GGT1 [142], CTSD (cathepsin D) [143], FASLG (Fas ligand) [144], CCR4 [145], FCRL3 [146] and ABCF1 [147] were revealed and regarded as diagnostic biomarker in pancreatitis.…”
Section: Discussionmentioning
confidence: 99%